2001
DOI: 10.12968/hosp.2001.62.2.2093
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin levels in patients with impaired renal function

Abstract: Cardiac troponins are important indicators of myocardial damage. Recent studies have shown that serum cardiac troponin levels are raised in at least 50% of patients with renal disease. The mechanisms and implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…27 It is unlikely that increased serum cTnI is the result of decreased clearance by the failing kidneys. cTnI is cleared by the reticulo‐endothelial system (RES), and renal failure should only have minor effects on RES 27 . Pericarditis secondary to uremia is a well‐documented condition in people affecting the subepicardium leading to the release of cTnI 28 .…”
Section: Discussionmentioning
confidence: 99%
“…27 It is unlikely that increased serum cTnI is the result of decreased clearance by the failing kidneys. cTnI is cleared by the reticulo‐endothelial system (RES), and renal failure should only have minor effects on RES 27 . Pericarditis secondary to uremia is a well‐documented condition in people affecting the subepicardium leading to the release of cTnI 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with normal renal function, cTnT levels will increase in the first 3 to 5 hours following myocardial infarction and remain high for up to 21 days, whereas their cTnI levels will increase in the first 3 hours and remain high for up to 7 days. According to recent studies, serum cardiac troponin levels are elevated in at least 50% of patients with renal disease (23). Therefore, for patients with amyloidosis who only have renal involvement, it remains unclear whether troponin reflects the degree of renal involvement and the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although the pathophysiology remains unclear, the role of uremic myopathy leading to rhabdomyolysis, decreased troponin clearance, and hypertrophic cardiomyopathy have been suggested. [25][26][27] Dessap et al, in a study of 125 patients with acute myocardial infarction found no association between creatinine clearance and peak troponin levels. 25 Similarly, we noticed a trend of increase in peak troponin levels until grade 3 renal function, but the trend disappears in grades 4 and 5 renal function.…”
Section: Discussionmentioning
confidence: 99%